Exploring nutritional potential of Atriplex hortensis - Rinchen, Tsewang; Singh, Narendra (Indian Horticulture, 2015)
Diversification of indigenous vegetables is now the best option to improve livelihood, food and health security. Atriplex, with emerging awareness appear to be potential to utilize marginal and degraded land. But to harness its full potential much more concerted efforts are needed. Around 14.5 tonnes/ha yield is obtained in 30-35 days. Considering the potential of Atriplex, more intensive research is needed, for assemblage, conservation and valuation of different resources which could be utilized for development of cultivars with high neutraceutical values coupled with high yield and resistance to biotic and abiotic stresses. To boost the quality, it is necessary to understand the stage of maturity and various process of product development. Understanding the medicinal values and related molecules is also essential. Atriplex which is a wonder plant could further be wonder to address may of challenges, through utilization of current knowledge and by addressing some of the researchable issues.